Visceral leishmaniasis in children: a cohort of 120 patients in a metropolitan city of Brazil - Rocha, Natália A.; Silva Júnior, Geraldo B.; Oliveira, Michelle J. C.; Abreu, Krasnalhia Lívia S.; Franco, Luiz F. L. G.; Silva, Marcos P.; Garcia, Ana Valeska V.; Daher, Elizabeth F. (The Turkish Journal of Pediatrics, 2011)
There are few studies regarding the clinical presentation of visceral leishmaniasis (VL) in children. The aim of this study was to investigate the clinical manifestations, major complications and causes of death in children with VL. A retrospective study was performed with pediatric patients (< or = 14 years old) with a diagnosis of VL in Fortaleza, state of Ceara, in Northeast Brazil. A total of 120 patients were included. The mean age was 5 +/- 3.9 years, and 53.4% were male. The main clinical manifestations at admission were: fever (94.2%), splenomegaly (94.2%), hepatomegaly (82.5%), anorexia (55%), malaise (47.5%), cough (41.6%), abdominal pain (27.5%), vomiting (25.5%), and diarrhea (16.6%). Acute kidney injury was found in 25% of the patients. The main complication during hospital stay was pulmonary infection, found in 27.5% (n = 33), leading to sepsis in 3 cases. Glucantime was the drug of choice in 90% (n = 108) of the cases, amphotericin B in 7.5% (n = 9) and AmBisome in 2.5% (n = 3). Death occurred in 4 cases (3.3%) due to sepsis (3 cases) and hemorrhagic complications (1 case). Visceral leishmaniasis is a frequent infection among children in our region. The main complications were pulmonary infection and acute kidney injury related to antiparasitic therapy, along with sepsis and hemorrhage.